Factors Influencing Consumers Preference in Foreign-Branded Local Food - Mahir Pradana; Taufiq Syahrir; Muhammad Diandri Darmawan (Proceedings of AICS - Social Sciences, 2017)
This research is designed to determine the factors influencing the purchase intention of Indonesian students, mainly in Bandung city, toward foreign-branded local foods. Purchase intention is explained with several variables: normative influence, brand consciousness, perceived quality, and emotional value. The result is summarized in this paper, which provides a critical review of the existing literatures, focusing especially on the question of whether foreign tags or names of products mostly appeal to students as buyers. The methodological approach is described by using exploratory factor analysis.